Automated Tomographic Assessment of Structural Defects of Freeze-Dried Pharmaceuticals - Müller, Patric; Sack, Achim; Dümler, Jens; Heckel, Michael; Wenzel, Tim; Siegert, Teresa; Schuldt-Lieb, Sonja; Gieseler, Henning; Pöschel, Thorsten (Aaps Pharmscitech, 2024)
The topology and surface characteristics of lyophilisates significantly impact the stability and reconstitutability of freeze-dried pharmaceuticals. Consequently, visual quality control of the product is imperative. However, this procedure is not only time-consuming and labor-intensive but also expensive and prone to errors. In this paper, we present an approach for fully automated, non-destructive inspection of freeze-dried pharmaceuticals, leveraging robotics, computed tomography, and machine learning.
CRIS-Team Scopus Importer:2024-07-05
Keywords: freeze-drying; lyopohilisate; non-destructive inspection; X-ray tomography